Inference about Monophyly of the Family Oedipodidae and the Classification of Subfamilies Based on 16S rDNA Sequences - Liu, Dian-Feng; Jiang, Guo-Fang (International Journal of Biotechnology for Wellness Industries, 2014)
Most of grasshoppers in the family Oedipodidae are the famous agriculture pests in China. However monophyly and the relationships among the subfamilies within this family are unclear up to now. Here the phylogeny of the Oedipodidae was reconstructed based on 16S rDNA sequence fragments by using Mekongiella kingdoni and Atractomorpha sinensis as outgroups under weighted MP, NJ and Bayesian criteria. The 408 bp fragments of mitochondrial 16S rRNA gene were sequenced for 15 species from 4 subfamilies of the family Oedipodidae, and the homologous sequences of other 15 species of grasshoppers were downloaded from the GenBank data library. The numbers of transitions and transversions among pairwise comparisons of the 16S fragments were respectively plotted against percentage sequence differences. Saturation of transitions was discovered, and transversions were not saturated with the increase of percentage sequence difference in the plots. All the individuals of the Oedipodidae excluding Trilophidia annulata were gathered together in the three trees. Our results are very different from the traditionary taxonomy of the Oedipodidae including 4 subfamilies. The Bryodemellinae is not supported as a subfamily, and neither Locustinae nor Oedipodinae are supported as a monophyletic group in this study.